Two New Species of Biting Midges of the Genus Forcipomyia Meigen from Ecuador (Diptera: Ceratopogonidae) - Hochman, Sabrina I. (2017)
Adults of two new species of biting midges in the subgenera Lepidohelea Kieffer and Metaforcipomyia Saunders of the genus Forcipomyia Meigen, F. (L.) ivani sp. nov. and F. (M.) aidae sp. nov., are described from specimens collected in Imbabura province, Ecuador at 2,320 meters above sea level. Color photographs and illustrations are provided of males and females of both new species which are compared with similar, related congeners in their respective subgenera. We also provide the first record of F. (Forcipomyia) catarinensis Marino & Spinelli from Ecuador.